POTENSI KHITIN/ KHITOSAN DARI KULIT UDANG SEBAGAI BIOKOAGULAN PENJERNIH AIR - Manurung, Manuntun (Jurnal Kimia (Journal of Chemistry); Vol. 5, No. 2 Juli 2011, 2012)
The potency of chitin/chitosan isolated from shrimp waste as coagulant to reduce turbidity of water have been studied in this research. The chitin/chitosan was isolated through some processes including deproteination, demineralization and deacetylation.The chitin/chitosan obtained was characterized using FTIR and the degree of deacetylation was calculated based on FTIR spectra. The deacetylation degree was found 64.86%, which mean the chitin mixed with chitosan or crude chitosan. In which using concentration 0.5% alumina can only reduce the turbidity of water by 54.21% while chitin/chitosan can reduce up to 90.37% the turbidity of water.
Keywords: chitin, chitosan, coagulan, turbid water